Impact of Resistance Training on Functional Capacity and Muscle Performance in Postmenopausal Women - Subashini Kirthiga Suhara (Multidisciplinary Journal of Akseprin Indonesia, 2025)
The objective is to investigate the impact of 12 weeks of high-speed resistance training (RT) compared to low-speed RT on muscle strength, measured by one repetition maximum leg press (1RMLP) and bench press (1RMBP), as well as dominant (HGd) and non-dominant maximum isometric handgrip strength, power, ball throwing (BT) ability, functional performance assessed through the 8-foot up-and-go test (UG) and sit-to-stand test (STS), and perceived quality of life in older women. Methods: Ninety elderly women were categorized into a high-speed resistance training group [EG, n = 30], a low-speed resistance training group [SG, n = 30], and a control group [CG, n = 30]. The SG and EG participated in an analogous 12-week resistance training program [3 sets of 10 repetitions at 40–75% of the one-repetition maximum (1 < RM) and BT], employing slow, controlled (3 seconds) concentric muscle actions for the SG and rapid, explosive (< 1 second) concentric muscle actions for the EG (20% reduced workload per exercise without BT). Results: The dependent variable exhibited enhancement in both RT groups throughout the 12-week training duration in clinically significant measures ranging from small to large; however, a notable difference was observed between the EG and SG regarding performance alterations in BT and UG (28% vs 23%, 21% vs 13%, p<0.01, respectively). No significant alterations were seen for the CG. Conclusion: Although a high-speed resistance training program yields greater enhancements in muscular power and functional task performance, both low-speed and high-speed resistance training therapies effectively increase functional capacity, muscle performance, and quality of life in older women